Edukasi Pentingnya Pemberian ASI Eksklusif pada Bayi di Puskesmas Gambesi - The, Fera; Hasan, Marhaeni; Saputra, Sadrakh Dika (Jurnal Surya Masyarakat, 2023)
Exclusive breastfeeding is crucial in supporting the growth and development of babies, such as increasing antibodies, protecting against infectious diseases, and several other benefits. Exclusive breastfeeding also has physical and psychological benefits for the mother. This service aims to improve the knowledge of pregnant women in Gambesi Community Health Center about the benefits of breast milk. The type of activities carried out in the form of health counseling related to the benefits of exclusive breastfeeding. The instrument used to measure the level of knowledge of pregnant women in the form of a questionnaire with 10 structured questions about breast milk, the measurement results of this questionnaire is the level of knowledge is good, enough and less. This activity was preceded by a pre-test to measure the level of knowledge of pregnant women before receiving counseling materials and followed by a post-test to measure the level of knowledge of pregnant women after receiving counseling materials. Counseling participants amounted to 62 people, after the counseling obtained some results, namely there is an increase in the percentage of good knowledge groups by 65%, sufficient knowledge groups by 35%, and no participants with less knowledge level were found.